A first course in control systems - Faris, Waleed Fekry; Ihsan, Sany Izan (IIUM Press, 2009)
Control system is one of the most important subjects in engineering that crossed the borders between many disciplines. Essential knowledge of the subject became a must after the rapid development in technology that made controls everywhere in all devices used in everyday life.